Implementation of Good Governance in Inclusive Public Services in Candisari District Semarang City - Pamirah Pamirah; Aris Toening W; Permadi Mulajaya (International Forum of Researchers and Lecturers, 2026)
This study aims to analyze the implementation of good governance principles in inclusive public services in Candisari District, Semarang City. The study used a descriptive qualitative approach with data collection techniques through questionnaires, interviews, and documentation. Research informants consisted of sub-district officials and community service users, including vulnerable groups. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the implementation of good governance principles in Candisari District has begun, but has not been running optimally. The principle of transparency has been attempted through the provision of service information and the use of digital media, but accessibility of information for vulnerable groups is still limited. The principle of accountability has not been fully realized, as indicated by the less than optimal performance of the Women and Children Protection Task Force (Satgas PPA) in carrying out its duties and the less than optimal inclusive public complaint mechanism. From the aspect of participation, community involvement, especially vulnerable groups, in the planning and decision-making process is still limited and unstructured. In addition, legal certainty and regional security stability are relatively conducive, but still require institutional strengthening and synergy between stakeholders. This study concludes that the implementation of good governance in Candisari District still faces institutional, participation, and service accessibility constraints, so a strategy is needed to strengthen governance to realize inclusive and sustainable public services.